Environmental Awareness Toward Issues and Challenges of Sustainable Consumerism in the Indian Apparel Industry - Shivani Jadhav and Asha Verma (Nature Environment and Pollution Technology)
This confirmatory study focused on studying the attitude and behavior as well as environmental awareness towards sustainable consumerism. The study also aimed to check if accountability on the part of brands and the government could enhance sustainability in the apparel industry. An empirical inquiry was conducted with 396 respondents, considering they are consumers with purchasing power. The collected data were analyzed using correlation and descriptive analysis. Based on the findings, consumers’ apparel use and brand accountability are positively associated. At the same time, it was found that the attitude and behavior of consumers are the least essential determinants for sustainable apparel consumption. This might imply that their optimistic outlook may not always translate into real purchase behavior, which is consistent with earlier studies. The results of this research provide a foundation for a better comprehension of the many factors, including the sustainability of a clothing brand or product, which may affect consumer behavior. This approach could help the fashion industry develop practical strategies and alter how people think about and utilize apparel in the future.